Immunogenicity of a trivalent human papillomavirus L1 DNA-encapsidated, non-replicable baculovirus nanovaccine. - Hansam Cho; Hee-Jung Lee; Yoon-Ki Heo; Yeondong Cho; Yong-Dae Gwon; Mi-Gyeong Kim; Ki Hoon Park; Yu-Kyoung Oh; Young Bong Kim (PLoS ONE)
Previously, we developed a non-replicating recombinant baculovirus coated with human endogenous retrovirus envelope protein (AcHERV) for enhanced cellular delivery of human papillomavirus (HPV) 16L1 DNA. Here, we report the immunogenicity of an AcHERV-based multivalent HPV nanovaccine in which the L1 segments of HPV 16, 18, and 58 genes were inserted into a single baculovirus genome of AcHERV. To test whether gene expression levels were affected by the order of HPV L1 gene insertion, we compared the efficacy of bivalent AcHERV vaccines with the HPV 16L1 gene inserted ahead of the 18L1 gene (AcHERV-HP16/18L1) with that of AcHERV with the HPV 18L1 gene inserted ahead of the 16L1 gene (AcHERV-HP18/16L1). Regardless of the order, the bivalent AcHERV DNA vaccines retained the immunogenicity of monovalent AcHERV-HP16L1 and AcHERV-HP18L1 DNA vaccines. Moreover, the immunogenicity of bivalent AcHERV-HP16/18L1 was not significantly different from that of AcHERV-HP18/16L1. In challenge tests, both bivalent vaccines provided complete protection against HPV 16 and 18 pseudotype viruses. Extending these results, we found that a trivalent AcHERV nanovaccine encoding HPV 16L1, 18L1, and 58L1 genes (AcHERV-HP16/18/58L1) provided high levels of humoral and cellular immunogenicity against all three subtypes. Moreover, mice immunized with the trivalent AcHERV-based nanovaccine were protected from challenge with HPV 16, 18, and 58 pseudotype viruses. These results suggest that trivalent AcHERV-HPV16/18/58L1 could serve as a potential prophylactic baculoviral nanovaccine against concurrent infection with HPV 16, 18, and 58.